Tourism village clusters: Potential for development at Jepara, Indonesia - Fafurida Fafurida; Shanty Oktavilia; Phany Ineke Putri; Lutfiana Nur Atika (Tourism, 2023)
The tourism sector is one of the leading national economic sectors in Indonesia and it has developed very rapidly. Efforts to improve the rural economy are also directed at tourism development. Central Java is a province with a number of tourist villages and development in some regions like Jepara Regency has locations that are close to each other. This research aims at identifying the cluster pattern of tourist village development in Jepara Regency, Central Java Province. It applies a quantitative approach using secondary data with a k-means cluster analysis. The results found that there are three clusters of tourist villages in Jepara Regency: (a) cluster 1 has six tourist villages which have high numbers of visitors, easy access, appropriate public and tourist facilities, but have few attractions and their locations are quite far from each other; (b) cluster 2 has eight tourist villages with many attractions, appropriate public facilities, close distances between locations and easy access, but have low numbers of visitors and limited tourist facilities; (c) cluster 3 has ten tourist villages, easy access, but a low rate of tourist visits, limited attractions, long distances between locations, and also limited public and tourist facilities.